Epidemiology, Patients' Journey and Healthcare Costs in Early-Stage Non-Small-Cell Lung Carcinoma: A Real-World Evidence Analysis in Italy - Diego Luigi Cortinovis; Valentina Perrone; Elisa Giacomini; Diego Sangiorgi; Margherita Andretta; Fausto Bartolini; Giuseppe Taurino; Marco Belfiore; Emilia Sicari; Luca Degli Esposti (MDPI AG, 2023)
This real-world analysis aims to estimate the epidemiology and economic burden related to early-stage non-small-cell lung carcinoma (eNSCLC) in the clinical practice Italian setting. An observational analysis was performed using administrative databases linked to pathological anatomy data, covering around 2.5 mln health-assisted individuals. From 2015 to mid-2021, eNSCLC patients staged II-IIIA treated with chemotherapy after surgery were included. Patients were stratified into those presenting loco-regional or metastatic recurrence during follow-up and annualized healthcare direct costs covered by the Italian National Health System (INHS) were estimated. In 2019-2020, the prevalence of eNSCLC was 104.3-117.1/million health-assisted subjects, and the annual incidence was 38.6-30.3/million. Data projected to the Italian population estimated 6206 (2019) and 6967 (2020) prevalent and 2297 (2019) and 1803 (2020) incident cases. Overall, 458 eNSCLC patients were included. Of them, 52.4% of patients had a recurrence (5% loco-regional-recurrence, 47.4% metastatic-recurrence). Healthcare total direct costs/patient averaged EUR 23,607, in particular, in the first year after recurrence, costs averaged EUR 22,493 and EUR 29,337 in loco-regional and metastatic-recurrence patients, respectively. This analysis showed that about one-half of eNSCLC patients stage II-IIIA experience a recurrence, and in recurrence patients, total direct costs were almost two-fold those of no-recurrence patients. These data highlighted an unmet clinical need, as the therapeutic optimization of patients at early stages.